2015
DOI: 10.1002/jmv.24161
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale multiplex polymerase chain reaction assay for diagnosis of viral reactivations after allogeneic hematopoietic stem cell transplantation

Abstract: Viral reactivations following hematopoietic stem cell transplantation are thought to result from the breakdown of both cell‐mediated and humoral immunity. As a result, many viruses could be reactivated individually or simultaneously. Using a multiplex polymerase chain reaction (PCR), we prospectively examined many kinds of viral DNAs at a time in 105 patients who underwent allogeneic hematopoietic stem cell transplantation. In total, 591 whole blood samples were collected weekly from pre‐ to 42 days post‐trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 20 publications
7
60
1
5
Order By: Relevance
“…The plasmid DNAs were synthesized by Nihon Techno Service Company, Ibaragi, Japan. Using the serially diluted plasmid DNAs as standards, we confirmed that a minimum of 50 copies of each virus could be detected by this system [Inazawa et al, ].…”
Section: Methodssupporting
confidence: 62%
See 2 more Smart Citations
“…The plasmid DNAs were synthesized by Nihon Techno Service Company, Ibaragi, Japan. Using the serially diluted plasmid DNAs as standards, we confirmed that a minimum of 50 copies of each virus could be detected by this system [Inazawa et al, ].…”
Section: Methodssupporting
confidence: 62%
“…Median age was 34 years (ranging from 6 months to 69 years) (Table ). Detailed patient characteristics were previously described [Inazawa et al, ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactivation of multiple herpesviruses has been reported in transplant recipients [157,158,159], patients with sepsis [160] and drug-induced hypersensitivity syndrome (DISS), also known as drug rash, or those with eosinophilia and systemic symptomology (DRESS) [161,162,163,164,165,166]. The temporal order in which these viruses are reactivated and whether they interact to contribute to symptomology remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Primers and probes for HHV types 1–8 and the PCR conditions have been described previously 16, 17 , as have the primers and probes for the other viruses 18 and the primers and probes for Candida 18S and Aspergillus 18S 10, 1921 . Amplification of the human β-globulin gene served as an internal positive extraction and amplification control.…”
Section: Methodsmentioning
confidence: 99%